Fabrication of thin-film silicon on insulator by separation by implanted oxygen layer transfer - Wei, Xing; Wu, Ai Min; Chen, Meng; Chen, Jing; Zhang, Miao; Wang, Xi; Lin, Cheng Lu (Journal of vacuum science & technology. B, Microelectronics and nanometer structures processing, measurement and phenomena, 2008)
In this article, the authors propose an improved approach—separation by implanted oxygen (SIMOX) layer transfer process—to fabricate thin-film silicon on insulator (SOI). The top Si layer, a low-dose SIMOX wafer, was transferred upside down onto a thermally oxidized Si handle wafer by a bonding technique and etch-stop thinning process. Spectroscopic ellipsometry indicated a thin-film SOI with the device layer of 147.5 ± 3.1 nm . An atomic-scale sharp interface between the device layer and buried oxide layer was observed by high-resolution transmission electron microscopy.